2011
DOI: 10.1073/pnas.1006328108
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein TRXR-1 and GSR-1 are essential for removal of old cuticle during molting in Caenorhabditis elegans

Abstract: Selenoproteins, in particular thioredoxin reductase, have been implicated in countering oxidative damage occurring during aging but the molecular functions of these proteins have not been extensively investigated in different animal models. Here we demonstrate that TRXR-1 thioredoxin reductase, the sole selenoprotein in Caenorhabditis elegans, does not protect against acute oxidative stress but functions instead together with GSR-1 glutathione reductase to promote the removal of old cuticle during molting. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 36 publications
3
87
2
Order By: Relevance
“…The lower pKa of a selenol and the higher nucleophilicity of a selenolate confers a type of "catalytic advantage" over Cys, when attacked position of thiol-disulfide interchange reaction. Replacement of Sec with Cys in TRXR-1 completely eliminated catalytic activity to reduce thioredoxin (Stenvall et al, 2011). Interestingly, the same Sec replacement in TRXR-1 as well as selenolate TRXR-1 successfully restored vital-dye staining defect, dependent on V-ATPase activity, which did not require thioredoxin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The lower pKa of a selenol and the higher nucleophilicity of a selenolate confers a type of "catalytic advantage" over Cys, when attacked position of thiol-disulfide interchange reaction. Replacement of Sec with Cys in TRXR-1 completely eliminated catalytic activity to reduce thioredoxin (Stenvall et al, 2011). Interestingly, the same Sec replacement in TRXR-1 as well as selenolate TRXR-1 successfully restored vital-dye staining defect, dependent on V-ATPase activity, which did not require thioredoxin.…”
Section: Discussionmentioning
confidence: 95%
“…development (Stenvall et al, 2011). Therefore, we asked whether the reduced V-ATPase activity in trxr-1(jh143) requires thioredoxin system by observing acridine orange uptake in the condition absent of cytoplasmic thioredoxin, TRX-1 (Jee et al, 2005).…”
Section: Thioredoxin Reductases In Caenorhabditis Elegansmentioning
confidence: 99%
“…In contrast to other animals, TRXR-1, an ortholog of the human enzymatic antioxidant thioredoxin reductase-1, has been reported to be the only selenoprotein in C. elegans [42][43][44]. Recent study showed that trxr-1 null mutant did not show increased sensitivity to oxidative stress after incubation in 2 mM H 2 O 2 for 2 h [45]. Further investigation will be needed to determine whether Se incorporates into enzymatic antioxidant selenoprotein and the precise mechanisms by which Se(IV) regulates TRXR-1 in C elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas we cannot exclude the possibility that there could be some rare cell types in mice in which replication is critically dependent on TrxR1, our efforts to date have failed to pinpoint any such cell types. Recently, a study was reported on disruption of TrxR1 in another metazoan, the nematode C. elegans (Stenvall et al, 2011). C. elegans has only a single TrxR protein, and this is the only Seccontaining protein in the worm genome (Stenvall et al, 2011).…”
Section: Requirements Of Disulfide Reductases For Replication In Rodementioning
confidence: 99%
“…Recently, a study was reported on disruption of TrxR1 in another metazoan, the nematode C. elegans (Stenvall et al, 2011). C. elegans has only a single TrxR protein, and this is the only Seccontaining protein in the worm genome (Stenvall et al, 2011). Surprisingly, although worms lacking TrxR1 show a molting defect due to an inability to reduce protein disulfides in the old cuticle to allow its removal, but like mouse livers lacking TrxR1 (Rollins et al, 2010;Suvorova et al, 2009), they show no evidence of oxidative stress or replicative insufficiency (Stenvall et al, 2011).…”
Section: Requirements Of Disulfide Reductases For Replication In Rodementioning
confidence: 99%